Al-Qur'an sebagai Sumber Agama Islam - Syaripudin, Ahmad (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2016)
As the divine revelation, al-Qurâ€™Än is not a tught product and Mohammadâ€™s creation. So that, those who say that al-Qurâ€™Än is a thought product and Mohammadâ€™s creation, are not right and irresponsibility. If we look at historically and the revelation process of al-Qurâ€™Än, it was not revealed by accident, but it was revealed periodically, little by litte and verse by verse. The use of its revealation depends on the place and social matters. From this aspect, some of the Qurâ€™anic verses are the answers for the social matters occures among the human beings. The knowledge of al-Qurâ€™Än includes the meaning, characteristic, names, descent time of al-Qurâ€™Än, Makkiyyah and Madaniyyah verses, AsbÄb al-NuzÅ«l, and so on.